Utilizing applications Nutrihas Pro for calculated fluid and electrolyte requirements for patient. - Rogahang, Christine; TASLIM, Nurpudji A; SYAUKI, Yasmin A; BUKHARI, Agussalim; AMINUDDIN, Aminuddin; ASHARI, Nur (Nutrición Clínica y Dietética Hospitalaria, 2025)
Background: Hospital malnutrition is a critical issue, particularly in regions like Makassar, Indonesia, where malnutrition rates surpass national averages. Malnourished patients often experience electrolyte imbalances and prolonged hospital stays, leading to increased healthcare costs. Despite the importance of accurate nutritional therapy, manual calculations are time-consuming and prone to human error, necessitating a more efficient solution. Objective: This study aims to assess the effectiveness of the Nutrihas-Pro application, developed to improve the accuracy and time efficiency of nutritional therapy planning compared to manual methods. Methods: An experimental repeated measures design was employed, involving 30 clinical nutrition residents at RSUP Dr. Wahidin Sudirohusodo. Participants manually calculated nutritional therapy and fluid/electrolyte needs for 60 patients and repeated the process using Nutrihas-Pro. Calculation times and accuracy were compared using paired-samples t-tests and chi- square tests. Results: The Nutrihas-Pro application significantly reduced calculation times (p = 0.000) compared to manual methods, without compromising the accuracy of fluid and electrolyte requirement calculations (p > 0.05). Patients displayed a high prevalence of electrolyte imbalance (68.3%), particularly hyponatremia (35%). Conclusion: Nutrihas-Pro improves time efficiency while maintaining calculation accuracy, making it a promising tool for nutritional therapy management. Further research is needed to address its limitations, including its reliance on internet connectivity and comparisons with other clinical calculator applications.